Confronting representative spectral structures of vocal tract pulse responses - Wojan, Z.; Lis, W.; Wojan, K. (Archives of Acoustics, 2006)
Before the resources of a number of ethnic language systems can be confronted, multiplelinguistic procedures must be applied to identify the possible common acoustic features in theutterances of the language users. There is a clear difference in the articulatory habits characteristicof the particular languages, which is why significant similarities must be sought inthe oblique fragments of speech that convey the information code (sense) rather than in theacoustic representation of free speech. The paper discusses methods and results of automaticclassification of selected lexemes of three language systems by confronting their digital representations.Digital representation includes sets of acoustic parameters as discussed in theprevious OSA papers, which the authors termed as: representative spectral structures of vocaltract pulse responses. Representative structures... were produced by cepstral smoothing ofaveraged acoustic parameters taken from multiple utterances by speakers of different gendersand ages. The paper includes spectrograms of the material used for confrontation and graphicillustrations of the results. Automatic classification of speech sounds of a pair of lexemes oftwo different languages is in fact the process of identifying the percentage proportions of convergentand divergent energies of lines in a set of parallel elements of both spectral matrixesbeing confronted, with time and frequency coordinates.